2007
DOI: 10.1111/j.1432-2277.2007.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after identical and compatible orthotopic liver transplantation for fulminant hepatic failure: a single center experience in UK

Abstract: Summary To analyze the outcomes between identical and compatible liver transplantation (OLT) for fulminant hepatic failure (FHF) from September 1984 to November 2005. The patients were divided in three groups; group 1 (identical), group 2 (compatible) and group 3 (incompatible), according to the donor‐recipient blood type matching. We analyzed several outcomes regarding mortality, patient and graft survival, incidence of acute graft rejection during the first postoperative month (30 days), incidence of biliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Studies that involved urgent indica-tions[ 15 , 17 , 19 , 20 , 33 , 34 , 39 , 40 , 42 ] had worse 1-year graft survival (OR = 0.37, 95%CI: 0.23-0.59 vs OR=0.70, 95%CI: 0.61-0.81; P = 0.01) but better 5-year patient survival (OR = 2.38, 95%CI: 0.86-6.63 vs OR = 0.79, 95%CI: 0.57-1.08, P = 0.043) for ABO-I LT than those for ABO-CT when compared to studies without urgent indications.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that involved urgent indica-tions[ 15 , 17 , 19 , 20 , 33 , 34 , 39 , 40 , 42 ] had worse 1-year graft survival (OR = 0.37, 95%CI: 0.23-0.59 vs OR=0.70, 95%CI: 0.61-0.81; P = 0.01) but better 5-year patient survival (OR = 2.38, 95%CI: 0.86-6.63 vs OR = 0.79, 95%CI: 0.57-1.08, P = 0.043) for ABO-I LT than those for ABO-CT when compared to studies without urgent indications.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported no statistical difference in graft survival, while others have demonstrated that patient survival is less in ABOcompatible recipients compared to ABO-identical recipients. ABO-identical OLT is still preferred (Aladag et al, 2006;Bjoro et al, 2003;Koukoutsis et al, 2007); Smith et al, 2000).…”
Section: Abo-incompatible Graftsmentioning
confidence: 99%
“…Possibly due to the fact that kidney transplant contains fewer GVH antibodies and GVH antibody-producing cells, GVH antibody-induced hemolytic anemia was mild and does not cause serious consequences in kidney transplantation. In liver transplantation, with presumably more GVH antibodies or GVH antibody-producing cells, Koukoutisis [6] and Bjoro [7] reported that ABO-compatible transplant recipients have significantly lower graft and patient survival compared to ABO-identical transplant patients. The intestine possesses the largest mass of lymphoid tissue of any solid organ in the human body [15].…”
Section: Discussionmentioning
confidence: 99%